Using hypnosis to disrupt face processing: mirrored-self misidentification delusion and different visual media - Connors, Michael H.; Barnier, Amanda J.; Coltheart, Max; Langdon, Robyn; Cox, Rochelle E.; Rivolta, Davide; Halligan, Peter W. (Frontiers in Human Neuroscience, 2014)
Mirrored-self misidentification delusion is the belief that one’s reflection in the mirror is not oneself. This experiment used hypnotic suggestion to impair normal face processing in healthy participants and recreate key aspects of the delusion in the laboratory. From a pool of 439 participants, 22 high hypnotisable participants (“highs”) and 20 low hypnotisable participants were selected on the basis of their extreme scores on two separately administered measures of hypnotisability. These participants received a hypnotic induction and a suggestion for either impaired (i) self-face recognition or (ii) impaired recognition of all faces. Participants were tested on their ability to recognise themselves in a mirror and other visual media – including a photograph, live video, and handheld mirror – and their ability to recognise other people, including the experimenter and famous faces. Both suggestions produced impaired self-face recognition and recreated key aspects of the delusion in highs. However, only the suggestion for impaired other-face recognition disrupted recognition of other faces, albeit in a minority of highs. The findings confirm that hypnotic suggestion can disrupt face processing and recreate features of mirrored-self misidentification. The variability seen in participants’ responses also corresponds to the heterogeneity seen in clinical patients. An important direction for future research will be to examine sources of this variability within both clinical patients and the hypnotic model.